DIETARY PATTERNS WERE ASSOCIATED WITH OBESITY PARAMETERS AMONG HEALTHY WOMEN - Syauqy, Ahmad; Noer, Etika Ratna; Fajrani, Alifia Mukti; Kurniawati, Dewi Marfu’ah; Purwanti, Rachma; Rahadiyanti, Ayu; Rahma, Devi Elvina (Journal of Nutrition College, 2020)
Background: Obesity is a growing major health problem in some developing countries including Indonesia. Study examined the association between dietary patterns and obesity parameters using both body mass index (BMI) and waist circumference (WC) among healthy women in Indonesia was still rare. Objectives: The objective of this study was to evaluate the correlation between dietary patterns and obesity parameters using BMI and WC among healthy women.Methods: This study used a cross-sectional design with consecutive sampling. Healthy women aged 20 and above were selected in this study. Dietary data were collected using a food frequency questionnaire (FFQ). For categorical data, chi-squared test was done to compare the differences in the characteristics of the subjects among tertiles of dietary patterns. For continuous variables, a general linear model test was used for comparison. To evaluate the association between dietary patterns and obesity parameters (BMI and WC), we used multiple linear regression analysis adjusting for multiple confounding variables (age, current smoking, current drinking, and physical activity). Results: Dietary pattern 1 consisted of 12 food items: snack cooked with oil, fish and seafood, processed food, organ meats, meat, poultry, rice- or flour-based products, staples cooked with oil, sugary drinks, refined dessert, and tea and coffee. Dietary pattern 2 consisted of 5 food items: eggs, light-colored vegetables, dark-colored vegetables, fruits, and soybeans. Dietary pattern 3 consisted of 7 food items: milk products, legumes, processed fruits, wholegrain, snacks cooked without oil, root crops, and jam/honey. Dietary pattern 1 was positively associated with obesity parameters including BMI and WC (P < 0.05); whereas, dietary pattern 2 and dietary pattern 3 were inversely correlated (P < 0.05).Conclusions: Our study find that dietary patterns were associated with BMI and WC among healthy women.